Das Janusgesicht Europas: Zur Kritik des kolonialen Diskurses - Großklaus, Götz (transcript, 2017)
Why is the mental program of colonialism still so topical all over the world? It has an after-effect in a multitude of literary texts that spread, normalize and legalize the core message of the racially inferior others. This book traces the suppressed colonial history of the European global power position, showing the continuity of the colonial process in its global integration up to today. The analysis of colonial events is conducted by means of fictional and non-fictional texts in the historical and systemic connection of colonial possession of global power. The European self-reflection therefore presents ways of how to liberate oneself from the unacknowledged after-effects of colonial actions and thinking.